The distinct clinical trajectory, metastatic sites, and immunobiology of microsatellite-instability-high cancers - Han, Shuting; Chok, Aik Yong; Peh, Daniel Yang Yao; Ho, Joshua Zhi-Ming; Tan, Emile Kwong Wei; Koo, Si-Lin; Tan, Iain Bee-Huat; Ong, Johnny Chin-Ann (Frontiers in Genetics, 2022)
Microsatellite-instability High (MSI-H) cancers form a spectrum of solid organ tumours known collectively as Lynch Syndrome cancers, occurring in a subset of colorectal, endometrial, small bowel, gastric, pancreatic and biliary tract cancers but also in prostate, breast, bladder, thyroid cancers. Patients with Lynch Syndrome harbour germline mutations in mismatch repair genes, with a high degree of genomic instability, leading to somatic hypermutations and therefore oncogenesis and cancer progression. MSI-H cancers have unique clinicopathological characteristics compared to their microsatellite-stable (MSS) counterparts, marked by higher neoantigen load, immune cell infiltration and a marked clinical response to immune checkpoint blockade. Patients with known Lynch Syndrome may be detected early through surveillance but some present with disseminated metastatic disease. The treatment landscape of MSI-High cancers, especially colorectal cancers, have undergone a paradigm shift and remains to be defined, with immune checkpoint blockade coming to the forefront of treatment strategies in the stage IV setting. We summarise in this review the clinical features of MSI-H cancers with a specific interest in the pattern of spread or recurrence, disease trajectory and treatment strategies. We also summarise the tumour immune landscape and genomic profile of MSI-H cancers and potential novel therapeutic strategies.